Founding family ownership and firm performance: Some evidence from the Italian stock market - Pierluigi Pierni; Dennis Marco Montagna; Mario Alessandro Maggi (Journal of Risk and Financial Management, 2022)
This study investigates the relationship between founding family ownership and firm performance in the Italian stock market. Making use of a precise definition of Founding family ownership factor, an empirical analysis on the stock monthly returns has been carried out, from an investor's point of view facing an asset allocation problem. Portfolios built on the basis of the Founding family factor show superior returns with respect to both a benchmark index and a portfolio strategy based on alternative (non-family-owned) firms on the market. Furthermore, there is evidence that an active role of family in the company governance, at least in Italy, may be beneficial for the superior performance of the Founding family portfolio. The results may suggest that the Founding family feature deserves attention in asset allocation.
Keywords: 650; factor portfolio model; family factor; portfolio management; style investing